2020
DOI: 10.1016/j.adro.2020.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Salvage Radiation Therapy for Recurrent Endometrial Cancer in Patients With No Prior Adjuvant Therapy: An Institutional Review

Abstract: Purpose After definitive surgery, women with early-stage, low-risk endometrial cancer are observed. However, some will require salvage radiation therapy for recurrence. The purpose of this study was to evaluate our experience using salvage radiation for recurrent endometrial cancer in patients who did not receive upfront adjuvant therapy. Methods and Materials Twenty-eight women with endometrial cancer who had undergone initial definitive hysterectomy without adjuvant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…reported in other series. [20][21][22][23] Furthermore, it may appear better than the local control rates reported by Kotsuma et al and Vargo et al 24,25 The present study supports a recent American Brachytherapy Society literature review, which found 2-5-year local control rates of 83%-100% and low significant late-term morbidities with the use of imageguided brachytherapy in vaginal recurrences of endometrial cancer. 10 The EBRT doses used for microscopic disease (45 Gy) within the present study are within the current guideline recommendations (45-50 Gy).…”
Section: Discussionsupporting
confidence: 83%
“…reported in other series. [20][21][22][23] Furthermore, it may appear better than the local control rates reported by Kotsuma et al and Vargo et al 24,25 The present study supports a recent American Brachytherapy Society literature review, which found 2-5-year local control rates of 83%-100% and low significant late-term morbidities with the use of imageguided brachytherapy in vaginal recurrences of endometrial cancer. 10 The EBRT doses used for microscopic disease (45 Gy) within the present study are within the current guideline recommendations (45-50 Gy).…”
Section: Discussionsupporting
confidence: 83%
“…Almost 40% of our series had definitive radical (chemo)radiotherapy, either primary or salvage therapy. The OS results for women receiving salvage treatment are comparable to other series [18][19][20]. Conversely, 5-year OS was poor, at just 23.8%, in the medically inoperable patients.…”
Section: F I G U R E 1 Overall Survival (A-by Age Group B-stage C-tre...supporting
confidence: 66%
“…In-field second LR after RT was observed in 56.6% of patients, in one study (20). The RT field for postoperative LR of uterine endometrial cancer is also the whole pelvis, including the prophylactic LN regions, and in some patients, a vaginal BT boost is often combined with RT (22)(23)(24). Studies have reported that infield second LR after RT was observed in 7.1-15.1% of patients (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The RT field for postoperative LR of uterine endometrial cancer is also the whole pelvis, including the prophylactic LN regions, and in some patients, a vaginal BT boost is often combined with RT (22)(23)(24). Studies have reported that infield second LR after RT was observed in 7.1-15.1% of patients (23,24). In a study that included patients receiving vaginal BT with and without whole pelvic RT, pelvic progressive disease was observed in 52.1% of the patients after RT (22).…”
Section: Discussionmentioning
confidence: 99%